Antiretroviral therapy alone versus antiretroviral therapy with a kick and kill approach, on measures of the HIV reservoir in participants with recent HIV infection (the RIVER trial): a phase 2, randomised trial - Fidler, S; Stöhr, W; Pace, M; Dorrell, L; Lever, A; Pett, S; Kinloch-de Loes, S; Fox, J; Clarke, A; Nelson, M; Thornhill, J; Khan, M; et al. (Elsevier, 2020)
Background: Antiretroviral therapy (ART) cannot cure HIV infection because of a persistent reservoir of latently infected cells. Approaches that force HIV transcription from these cells, making them susceptible to killing—termed kick and kill regimens—have been explored as a strategy towards an HIV cure. RIVER is the first randomised trial to determine the effect of ART-only versus ART plus kick and kill on markers of the HIV reservoir.